Innovations in Stress Urinary Incontinence: A Narrative Review - Tamas Szabo; Melinda-Ildiko Mitranovici; Liviu Moraru; Dan Costachescu; Laura Georgiana Caravia; Elena Bernad; Viviana Ivan; Adrian Apostol; Mihai Munteanu; Lucian Puscasiu (Medicina)
Urinary incontinence is characterized by the involuntary leakage of urine. The primary cause of stress urinary incontinence in women is the weakening of the pelvic floor muscles. Stress urinary incontinence (SUI) is a significant global health problem that impacts mainly middle-aged women, with a severe impact on their quality of life. Traditional diagnostic methods and treatments often fail, although technological innovations have improved diagnostic accuracy, such as specific questionnaires or transperineal ultrasound. While medical therapies and surgical procedures are continuously being developed, controversies about the correct choices regarding diagnostic and treatment methods continue to exist. The aim of our review was to identify the innovative diagnostic tools and effective treatment procedures for SUI. A narrative review was conducted due to the heterogeneity of the studies. New methods for diagnosis and treatment have gained ground, and we have covered them in our review; however, the field continues to expand. A personalized approach to diagnosis is also a requirement because of the limitations of conventional urodynamic studies, and we emphasize the importance of such personalization in enhancing clinical decision making. Future medical strategies that combine both preventive and therapeutic care are desirable. Newer technologies were brought to light in this review, including stem cell therapy and laser therapy.